HUMAN MONOCLONAL ANTIBODIES TO TNF-? - AGENT OF CHOICE IN TREATMENT OF SEVERE JUVENILE RHEUMATOID ARTHRITIS WITH UVEITIS - A.O. Lisitsyn; E.I. Alexeeva; S.I. Valieva; T.M. Bzarova; R.V. Denisova; N.А. Karagulyan; A.M. Chomachidze; K.B. Isaeva ("Paediatrician" Publishers LLC, 2010)
The article presents a case report of an early debut and severe clinical course of juvenile rheumatoid arthritis with eyes' lesion. Authors describe successful administration of human monoclonal antibodies to tumor necrotizing factor (TNF) - adalimumab. In 2 weeks of treatment the morning joint stiffness was stopped, in 4 weeks exudative alterations in affected joints were vanished, and the range of their motions increased. Results of laboratory tests: ESR and concentration of C-reactive protein in plasma were normalized in 6 weeks. Adalimumab initiated development of remission of bilateral uveitis in 8 weeks. Key words: children, juvenile rheumatoid arthritis, rheumatoid uveitis, adalimumab, treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(3):140-146)